Aesthetic-functional rehabilitation through complete denture: clinical case report (Research, Society and Development, 2021)
Objective: The aim of this case report was to demonstrate the importance of oral rehabilitation with mucus-supported upper and lower total dentures for an improvement in the patient's oral health. In these cases, patients cannot stand the lack of teeth, as they interfere directly in their social life, impairing their eating and speech and their self-esteem. Methodology: This is a case report, based on the literature, which is a method that provides knowledge and results of studies in practice, with a broad methodological approach incorporating concepts, review of theories, evidence and analysis of methodological problems (Gonçalves, 2021). Clinical case report: A case report was presented where the patient attended the Fametro dental clinic, complaining that she was not satisfied with her upper prosthesis, since she had never used a lower prosthesis, and that due to the lack of prosthesis The lower one found difficulty in chewing, having pasty foods as his main diet. Final considerations: After the treatment, a satisfactory result was achieved for both the professional and the patient, restoring its aesthetics and function.